Wal-Mart:Can it Succeed in India? - Chopra, Komal (Indian Journal of Marketing, 2011)
India is seen as an emerging market for retail by global retailers. In 2009, A.T. Kearney’s Global Retail Development Index (GRDI), ranked India as the most emerging destination for retail. However, to protect its own retail industry, the Government of India has permitted only 51% FDI for "single brand retail". This has deterred many multi-brand retailers to enter India in the field of retailing. However, FDI up to 100% is allowed under the automatic route for cash and carry wholesale and export trading. An analysis by A.T. Kearney reveals that organized retail in India accounts for only 6% of the total retail market. In November 2006, Wal-Mart of US entered into a 50:50 joint venture with Bharti Enterprises of India to enter the wholesale sector as well as back end partner. Wal-Mart’s failure in South Korea, Germany and Japan has raised several apprehensions about its success in India. The article analyses the opportunities and challenges that Wal-Mart will face in India. The paper concludes with the discussion on whether the failure of Wal-Mart in three major countries and diverse consumer behaviour in India can be taken as a backdrop to predict its future in India.